Policy change in Austrian higher education : indications of a new approach - Gruber, Karl Heinz [Verfasser] (My University, 1991)
"Despite significant expansion in participation over the last three decades, Austrian higher education has been slow to change either its elitist self-concept or structure. But, as is the case elsewhere, the Austrian academic community is beginning to be confronted with such concepts as 'efficiency', 'strategic planning', 'deregulation', and 'performance evaluation'. Inadequate admission policies, extreme overcrowding, and high dropout rates are but three factors placing pressure on Austrian higher education to reform. The system is not only in need of increased budget allocations, but also requires new policies to guide it into the 21st Century." (author's abstract) ((en)) Der Aufsatz analysiert die Entwicklung des Hochschulsystems in Österreich von 1960-1990. Ungeeignete Zugangsstrategien, extreme Überfüllung und hohe Abbrecherquoten zwingen zu Reformen; mit erhöhten Haushaltszuweisungen ist es nicht getan, das System erfordert neue hochschulpolitische Strategien. (IAB)
Politischer Wandel im österreichischen Hochschulsystem. Anzeichen für einen neuen Ansatz
Keywords: Hochschulpolitik; Hochschulreform; Quantitative Angaben